The role of bHLH-PAS transcription factors in endoplasmic reticulum stress - Krauze, Izabela; Krzystek-Korpacka, Małgorzata; Maciejewska, Kamila; Greb-Markiewicz, Beata (Frontiers in Molecular Biosciences, 2025)
The bHLH-PAS protein family consists of transcription factors that are involved in the regulation of key physiological processes such as the response to hypoxia, circadian rhythms, the detoxification of xenobiotics, and metabolic homeostasis. These proteins act as environmental sensors, integrating diverse signals into transcriptional responses. In recent years, increasing attention has been paid to their role in regulating endoplasmic reticulum stress (ER stress), which is an adaptive cellular response to disturbances in protein-folding. Prolonged or severe ER stress can activate the unfolded protein response (UPR) and apoptotic pathways, contributing to the development of numerous disorders, including neurodegenerative, cancerous, and inflammatory diseases. This review focuses on the functions of bHLH-PAS proteins, such as AHR, HIF, SIM, NPAS1-4, and CLOCK, with particular emphasis on their potential role in modulating ER stress. Molecular mechanisms through which these proteins regulate responses to hypoxia and other cellular stressors are also discussed, with a focus on their importance in maintaining homeostasis and their potential as therapeutic targets.